2017
DOI: 10.4314/jae.v21i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Agronomic Practice in Management of the Tomato (<i>Solanum lycopersicon</i> L.) Yellow Leaf Curl Virus in Central Region of Ghana

Abstract: The study assessed farmers' awareness of tomato yellow leaf curl virus (TYLCV) Efutu (49.5±1.19%, 25.29±0.9%), and Mfantseman (42.1±2.7%, 21.41±0.8%) respectively. In conclusion, TYLCV was highly prevalent in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…This also implies that processors are well experienced in marketing of such processed vegetable crops. This agrees with the findings of Asare et al (2017) who reported in Central Region of Ghana had 6-10 years of marketing experience while 54.44% of the retailers had only 1-5 years of marketing experience.…”
Section: Results and Discussion Socio-economic Characteristics Of The...supporting
confidence: 92%
“…This also implies that processors are well experienced in marketing of such processed vegetable crops. This agrees with the findings of Asare et al (2017) who reported in Central Region of Ghana had 6-10 years of marketing experience while 54.44% of the retailers had only 1-5 years of marketing experience.…”
Section: Results and Discussion Socio-economic Characteristics Of The...supporting
confidence: 92%